Indonesian University Graduates’ English Competence for Facing the Asean Economic Community (AEC) - Rentauli Mariah Silalahi (IJEE (Indonesian Journal of English Education), 2017)
ABSTRACT The ASEAN Economic Community (AEC) has been started since 2015, yet Indonesia is not ready because many Indonesian graduates are not ready with adequate English competence. This means many students graduated from universities with poor English proficiency. To investigate this unpreparedness, this study was carried out to one of the universities in Indonesia by doing documents analysis towards the university’s curriculum and the graduates’ English proficiency as measured by TOEFL ITP test. After the analysis, this study found out that the university was not yet ready to produce graduates who are competent in English because the graduates’ TOEFL ITP average score for all years was 457. From 944 graduates batch 2001 to 2013, there were only 2 percent who could achieve a TOEFL ITP score of 550 or more. These research findings will be very useful for stakeholder and any other universities for reflection on their preparation for producing graduates who are competent in English.   ABSTRAK Masyarakat Ekonomi ASEAN (MEA) telah dimulai sejak 2015, namun Indonesia belum siap karena banyak lulusan Indonesia belum memiliki kompetensi bahasa Inggris yang memadai. Ini berarti banyak siswa lulus dari universitas dengan kemampuan bahasa Inggris yang buruk. Untuk mengetahui ketidaksiapan ini, penelitian ini dilakukan pada salah satu universitas di Indonesia dengan melakukan analisis dokumen terhadap kurikulum universitas dan kemampuan bahasa Inggris lulusan yang diukur dengan tes TOEFL ITP. Penelitian ini menemukan bahwa universitas tersebut belum siap untuk menghasilkan lulusan yang kompeten dalam bahasa Inggris karena nilai rata-rata TOEFL ITP lulusan untuk semua tahun adalah 457. Dari 944 lulusan, angkatan 2001 sampai 2013, hanya ada 2 persen saja yang bisa meraih nilai TOEFL ITP 550 atau lebih. Temuan penelitian ini akan sangat bermanfaat bagi pemangku kepentingan dan universitas lain untuk merenungkan persiapan mereka untuk menghasilkan lulusan yang kompeten dalam bahasa Inggris.How to Cite: Silalahi, R. M. (2017). Indonesian University Graduates’ English Competence for Facing the Asean Economic Community (AEC). IJEE (Indonesian Journal of English Education), 4(1), 71-83 doi:10.15408/ijee.v4i1.3457DOI: http://dx.doi.org/10.15408/ijee.v4i1.3457